PENGARUH KESADARAN WAJIB PAJAK DAN PROGRAM PEMUTIHAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA KANTOR SAMSAT CIMAHI - Dwi Anjarwati, Putri; Dherian Rizki, Nonon; Kibet Lesmana, Kusnadi (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2025)
Motor Vehicle Tax is one of the regional taxes that serves as an important source of revenue for provincial governments in Indonesia. The compliance of motor vehicle taxpayers is a crucial factor in increasing regional tax revenue. However, many taxpayers are still found to delay or even avoid fulfilling their tax obligations. This study aims to examine the influence of Taxpayer Awareness and the Tax Amnesty Program on Motor Vehicle Taxpayer Compliance at the Cimahi Samsat Office. The research uses a quantitative method with a descriptive approach. Data was collected through questionnaires distributed directly to 100 respondents as the research sample. The data analysis technique used is multiple linear regression, processed using SPSS version 29. The results of this study indicate that both partially and simultaneously, Taxpayer Awareness and the Tax Amnesty Program have a significant influence on Motor Vehicle Taxpayer Compliance at the Cimahi Samsat Office.